Nanoshaping of glass forming metallic liquids by stretching: evading lithography. (18th December 2018) - Hu, Zhonglue; Meduri, Chandra Sekhar; Blawzdziewicz, Jerzy; Kumar, Golden
Abstract: Lithography-free nanomanufacturing by elongation and fracture of glass forming metallic liquid is presented. The viscous metallic liquid confined in a cavity is laterally downsized to nanoscale by stretching. The extent of size-reduction can be controlled by tuning the active volume of liquid and the viscous and capillary stresses. Very high aspect-ratio metal nanostructures can be fabricated without using lithography or expensive molds. A systematic study is performed using glass forming Pt-Cu-Ni-P alloy to understand the effects of viscosity, surface tension, pulling velocity, and cavity size on the evolution of cylindrical liquid column under tension. The results are quantitatively described using a phenomenological model based on lubrication theory and surface tension induced breakup of liquid filaments. A new manufacturing approach based on variable pulling velocity and/or spinning of metallic liquid is proposed for fabrication of complex geometries.